IMPROVE Learning Model and Learning Independence: Influence and Interaction on Mathematics Problem-Solving Abilities in Islamic Boarding School. (February 2020) - Yasin, Muhamad; Huda, Syamsul; Putra, Fredi Ganda; Syazali, Muhammad; Umam, Rofiqul; Widyawati, Santi
Abstract: Problem-solving ability is a basic ability in the process of learning mathematics. The purpose of this study is to determine whether there is an effect of the IMPROVE learning model on mathematics problem-solving abilities, the effect of students' learning independence on mathematics problem-solving abilities, and the interaction between learning model and learning independence in term of mathematics problem-solving abilities. The research method used was quasi-experimental with post-test-only control group design. The data analysis technique used was the analysis of the variance of two unequal cells. The results showed that there were differences in mathematics problem-solving abilities between students who had high, medium, and low learning independence. The values of the results of the comparison are FAobserved = 3.271 and FAcritical = 3.170, FBobserved = 6.945 and FBcritical = 4.020, FIobserved = 0.554 and FI critical = 3.170 at a significance level of 5%. Based on the norm, where Fobserved > Fcritical, H0 is rejected. So, it can be concluded that there is an influence between the IMPROVE learning model and mathematics problem-solving abilities, there is an influence between learning independence and mathematics problem-solving abilities, and there is no interaction between the IMPROVE learning model and the learning independence on mathematics problem-solving abilities.